Salt to the sea - Sepetys, Ruta (Penguin Books, 2017)
"Winter 1945. Four refugees. Four secrets. Each one born of a different homeland; each one hunted, and haunted, by tragedy, lies, war. As thousands desperately flock to the coast in the midst of a Soviet advance, four paths converge, vying for passage aboard the Wilhelm Gustloff, a ship that promises safety and freedom. But not all promises can be kept." -- Page [4] cover.
"As World War II draws to a close, refugees try to escape the war's final dangers, only to find themselves aboard a ship with a target on its hull." -- provided by publisher.
Includes excerpt from Between Shades of Gray.
Includes interviews with Wilhelm Gustloff survivors and experts.
Includes bibliographical references (pages 387-388).
Keywords: Wilhelm Gustloff (Ship) -- Juvenile fiction; World War, 1939-1945 -- Juvenile fiction; Refugees -- Juvenile fiction; Transatlantic voyages -- Juvenile fiction; Young adult fiction; Historical fiction